A new steepest descent method with global convergence properties - Abidin, Z.Z.; Mamat, M.; Rivaie, M (2016)
One of the earliest and the best method to minimize a function is the classical steepest descent (SD) method. In this paper, a new modification of SD method is suggested using a new search direction, d k. The numerical results are presented based on number of iterations and CPU time. It shows that the new d k are efficient when compared to the classical SD.